Italians Do It … Less. COVID-19 Lockdown Impact on Sexual Activity: Evidence From a Large Representative Sample of Italian Adults - Gorini, Giuseppe; Odone, Anna; Lugo, Alessandra; Fanucchi, Tiziana; Gallus, Silvano; Bosetti, Cristina; Pacifici, Roberta; Amerio, Andrea (Journal of Epidemiology, 2021)
Background: To explore how sexual activity was impacted by coronavirus disease 2019 (COVID-19) lockdown measures in the general adult population.Methods: A cross-sectional survey was conducted among 6,003 Italian adults aged 18–74 years who were representative of the Italian general population. Study subjects were recruited at the time of the nationwide stay-at-home order (from April 27 to May 3, 2020). We identified characteristics associated with decreased frequency of sex during lockdown, differentiating between cohabiting and non-cohabiting subjects.Results: Over one-third (35.3%) of Italians reported to have changed their sexual activity during lockdown (8.4% increased and 26.9% decreased). When focusing on cohabitants (N = 3,949, 65.8%), decreased sexual activity (20.7%) was more frequently reported by men (22.3%; compared to women, multivariable odds ratio 1.23; 95% confidence interval, 1.05–1.44), younger subjects (P for trend <0.001), more educated subjects (P for trend = 0.004), subjects living in smaller houses (P for trend = 0.003), and those reporting longer time spent outdoors before the lockdown (P for trend <0.001).Conclusions: COVID-19 lockdown drastically altered people’s day-to-day life and is likely to have impacted lifestyle habits and behavioral risk factors, including sexual attitudes and practice. This is the first national population-level study exploring changes in sexual life in this COVID-19 era. As we report sexual practice to have been affected by lockdown restrictions, we suggest that the mental health, social, and other determinants of these changes are to be explored beyond imposed social distancing.